Integrating Translanguaging in Students’ Writing: A Descriptive Qualitative Study at the English Department of the University of Mataram - Misrohatun, Misrohatun; Melani, Boniesta Zulandha; Apgrianto, Kurniawan (Papanda Publisher, 2026)
Academic writing in EFL contexts remains challenging due to simultaneous demands on content, grammar, vocabulary, and rhetoric. While translanguaging—the dynamic use of multiple languages—has gained attention as a meaning-making resource, its application and limitations in university-level argumentative writing in Indonesia are under-explored. This descriptive qualitative study involved 28 third-semester English Education students at the University of Mataram enrolled in an Argumentative Writing course. Data were collected through classroom observations (three sessions), questionnaires (N=28), and semi-structured interviews (n=5), then analyzed using thematic analysis with triangulation. Students frequently employed translanguaging across writing stages: bilingual reading, mixed-language discussion, L1 idea generation and drafting, tool-assisted translation, and revision. Twenty-six students wrote initial drafts in Bahasa Indonesia before translating. However, they reported difficulties in idea transfer, producing natural English sentences, lexical equivalence, and maintaining focus during language switching. Translanguaging facilitated idea development and reduced writing anxiety but posed cognitive and linguistic challenges in achieving academic English norms. Findings support a shift toward pedagogies that strategically integrate students’ full linguistic repertoires while providing targeted support for L2 accuracy.